Mephisto [videorecording (DVD)] - Szabó, István, 1938-; Szabó, István, 1938-; Brandauer, Klaus Maria; Janda, Krystyna; Hoppe, Rolf; Mann, Klaus, 1906-1949 (Kino Classics, 2020)
When an actor agrees to stay in Germany under the Nazi regime, he finds that the fame he has been seeking comes at the cost of his soul.